Effect of pretreatment and drying methods on quality of value-added dried aonla (Emblica officinalis Gaertn) shreds - Prajapati, V. K. (Springer-Verlag, 2010)
Value added dried Indian gooseberry (aonla) shreds were prepared using aonla fruits of cv. ‘NA-7’. Two blanching methods (hot water and potassium metabisulphite (KMS) at 0.1%) and two drying methods (solar and hot air oven drying) were tried for the production of aonla shreds. Common salt, black salt and ginger juice were mixed for enhancing sensory quality of the product. The best product was obtained with KMS blanching and drying in solar dryer with added common salt at 3%. The most acceptable product had ascorbic acid content 298.3 mg/100 g, tannin 2.4%, acidity 2.6%, reducing sugar 3.0%, non-reducing sugar 21.0% and total sugar 24.0%. The recovery was 8.0–8.5%.